2021
DOI: 10.1039/d1gc02919c
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable production of levulinic acid and its derivatives for fuel additives and chemicals: progress, challenges, and prospects

Abstract: The research progress on the production of levulinic acid and its derivatives for fuel additives and chemicals from various sugars and biomass feedstocks have been comprehensively reviewed, focusing on the chemical processes and mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 418 publications
0
51
0
Order By: Relevance
“…Organic acids stress factors mainly refer to formic acid and acetic acid. Acetic acid is mainly formed by deacetylation of the acetyl group of hemicelluloses, while formic acid can be formed by degradation of sugars [ 49 ]. The concentrations of organic acid stress factors in the hydrolysate are relatively higher than furans and phenols.…”
Section: Response Of S Cerevisiae To Stress Factorsmentioning
confidence: 99%
“…Organic acids stress factors mainly refer to formic acid and acetic acid. Acetic acid is mainly formed by deacetylation of the acetyl group of hemicelluloses, while formic acid can be formed by degradation of sugars [ 49 ]. The concentrations of organic acid stress factors in the hydrolysate are relatively higher than furans and phenols.…”
Section: Response Of S Cerevisiae To Stress Factorsmentioning
confidence: 99%
“…It is usually observed that high-temperature conditions are required for activating solid acid catalysts which is the major problem during their synthesis. 107,108,111 The harsh condition also breaks the concept of green chemistry. Consequently, there is a need to construct special equipment for this process that makes it costly and non-green.…”
Section: Mechanism Of the Conversion Of Levulinic Acid To Levulinate ...mentioning
confidence: 99%
“…Levulinic acid is produced from lignocellulosic biomass and derived sugars attained by the biofine process, which is the only process used industrially. The biofine process is a high‐temperature process where sulfuric acid is used as a homogeneous catalyst for modifying lignocellulosic biomass (LCB) raw materials to LA and its derivatives 107,108 . This process follows two stages: in the first stage, various adjustments are done in reaction conditions such that in the first reactor different processes of LCB fractionation, sugar dehydration and polysaccharide hydrolysis take place while conversion to LA from intermediates takes place in the second reactor.…”
Section: Commercial‐scale Production and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Levulinic acid (LA) is a platform chemical derived from lignocellulose biomass with great potential to produce a wide range of valuable chemicals [1][2][3][4][5]. Levulinate esters (e.g., ethyl levulinate, EL) are considered as an alternative to LA due to their specific physicochemical properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%